The impact of change in oil prices on economic growth in Iraq for the period (2005- 2017), an analytical study - طه, حسام الدين (Journal of Petroleum Research and Studies, 2021)
Oil has become the direct role in the management of economic growth, and in moving the scenes of global conflicts because of the world's increasing need for the energy required by social and economic development and demographic growth. The current situation needs to analyze the oil sector and study the various aspects related to it. The research aims to analyze the changes in oil prices in the indicators of economic growth in Iraq for the period (2005-2017). According to statistical analysis, the relationship between the average price of Iraqi oil and the national income is a positive one, and the average price of Iraqi crude oil and the average per capita national income per capita is a direct correlation between the average price of Iraqi oil and GDP. The study recommended activating the fiscal policy in the Iraqi economy by stimulating the mechanisms of customs tax policy because it is important in enriching the budget with multiple sources of taxation so that the mechanisms of fiscal policy work to achieve economic goals, namely raising private savings rates and stimulating investment decisions.